Prospecting New Antimicrobial Peptide from Gracilaria spp. Active-peptide Hydrolysate against Pathogenic Bacteria using Proteomic Approach - Chandra, Klara Kharisma Bunga; Nuringtyas, Tri Rini; Raharjo, Tri Joko (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
Our study focused on unveiling the tropical red algae Gracilaria spp. Active-peptide materials from the central region of Java Island, Indonesia. We described the protein isolation, hydrolysis, purification, and method to test its potency against pathogen Staphylococcus aureus IFO 12576 and Eschericia coli IFO 3301, followed by molecular docking analysis. TCA/acetone precipitation was used to isolate Gracilaria spp. proteins, and the hydrolysis was done by trypsin digestion with an effective yield to provide antibacterial activity. The disk diffusion method showed promising inhibition and continued with a confirmation test using microdilution, which implied bacteriostatic inhibition with a minimum concentration of 40 µg/ml, from one potent fraction. Further characterizations were conducted using a proteomic approach. LC-HRMS was used for peptide sequencing in the potent fraction with prospective peptides identified along with its physical properties. Molecular docking simulations were used to investigate the degree of interactions using binding affinities score (kcal/mol), with the target of receptor DraE adhesin subunit (2JKJ) of Escherichia coli binds chloramphenicol. We proposed the interactions model of peptides GP1 and GP4 against targeted peptides. Our model GP4.1 and GP4.2 model (VVINADAK) were found to have high binding affinities with the energy score of -10,6 and -10,8 kcal/mol, respectively by the different sites of binding than chloramphenicol succinate.